Radiation Damage as a Possible Metal Chronometer for Pre-Detonation Nuclear Forensics - Edward T. Peskie; Howard L. Hall (International Journal of Nuclear Security, 2015)
The better we can determine how long ago nuclear material was made, the sharper our tools for investigating seized nuclear materials. This paper examines the effects of radiation damage caused by the decay of uranium isotopes, and assesses how experts in nuclear forensics could use the analyses of these damaged regions to determine how much time has passed since metal samples were formed. It also draws parallels from fission track dating studies of mineral samples under geologic time, and proposes modifications to past publications on α-recoil track dating in order to determine the time since a metal sample was cast or formed.
Keywords: uranium; forensics; chronometry; alpha decay